Performance and economic evaluation of solar rooftop systems in different regions of Thailand - Yoomak, Suntiti; Patcharoen, Theerasak; Ngaopitakkul, Atthapol (My University, 2019)
Solar rooftop systems in the residential sector have been rapidly increased in the term of installed capacity. There are various factors, such as climate, temperature, and solar radiation, that have effects on solar power generation efficiency. This paper presents a performance assessment of a solar system installed on the rooftop of residence in different regions of Thailand by using PSIM simulation. Solar rooftop installation comparison in different regions is carried out to evaluate the suitable location. In addition, three types of solar panels are used in research: monocrystalline, polycrystalline, and thin-film. The electrical parameters of real power and energy generated from the systems are investigated and analyzed. Furthermore, the economic evaluation of different solar rooftop system sizes using the monocrystalline module is investigated by using economic indicators of discounted payback period (DPP), net present value (NPV), internal rate of return (IRR), and profitability index (PI). Results show that the central region of Thailand is a suitable place for installing solar rooftop in terms of solar radiation, and the temperature has more solar power generation capacity than the other regions. The monocrystalline and polycrystalline solar panels can generate maximum power close to each other. All solar rooftop sizes with the Feed-in Tariff (FiT) scheme give the same DPP of 6.1 years, IRR of 15%, and PI of 2.57 which are better than the cases without the FiT scheme. However, a large-scale installation of solar rooftop systems can receive more electrical energy produced from the solar rooftop systems. As a result, the larger solar rooftop system sizes can achieve better economic satisfaction.
Keywords: Economic evaluation; Single-phase grid-connected solar system; Solar energy; Solar rooftop